The Influence Of Work Life Balance And Work Stress On Work Productivity Of Employess At Pegadaian Sub-Branch Dinoyotangsi Surabaya - Annisa Ramadhania Hariani; Agus Frianto (International Journal of Social, Economic, and Business, 2024)
This study aims to determine the impact of work-life balance and work stress on work productivity. Data were analyzed using Multiple Linear Regression techniques with SPSS Version 26. The sample consisted of 43 respondents, drawn from employees of a pawnshop company in Surabaya, using a saturated sampling technique. The statistical results show that work-life balance does not significantly influence work productivity. Conversely, work stress has a significant positive impact on work productivity. Collectively, the statistical results indicate that work-life balance and work stress together have a significant positive influence on work productivity.